ISOLASI METABOLIT SEKUNDER DAN UJI TOKSISITAS EKSTRAK METANOL DAUN TANAMAN Cerbera odollam Gaertn. (APOCYNACEAE) - Rissan Ramaesy Tobing; Hilwan Yuda Teruna; Yuharmen ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cerbera odollam Gaertn is a plant found in Indonesia and used as a medicine. Isolationof its secondary metabolites and toxicity assay on leaves of this plant have been doneby macerating method with methanol solvent. The separation was carried out by vacuum liquid chromatography (VLC) and column chromatography, respectively. Characterization of the fractions was established using UV-Vis, FT-IR, and NMR. Toxicity assay was conducted by Brine Shrimp Lethality Test (BSLT) method. The LC 50 of 2 th , 4 th to 11 th fractions of the methanol extract were 874.78; 1076.71; 7.88; 0.85; 3.02; 0.23; 8.62; 3.94; 223.46; and 168.23 ppm respectively. The 3 th fraction was not toxic, where as other fractions were toxic and potential as anticancer.